GAMBARAN PENGRETAHUAN SELF MANAGEMENT DIABETES MELLITUS TIPE 2 (LITERATURE REVIEW) - Rika Nurhayati; Tri Hapsari Retno A; Yulida S; Ai Rokhayati (Jurnal Kesehatan Siliwangi, 2020)
Diabetes Mellitus is a series of metabolic disorders due to the pancreas not producing enough insulin, causing insulin deficiency both absolute and relative, resulting in an increase in blood glucose concentration, Self-management is a complex activity including the ability to control a condition and cognitive effect, behavior and response emotionally in maintaining the needs of quality of life, there are 5 pillars of self-management among them education, medical nutrition therapy, pharmacological therapy, physical exercise and blood sugar monitoring. The purpose of this study was to determine the description of self-management of diabetes mellitus type 2The method used in this study is a systematic literature review, with secondary data collection techniques obtained by 4 journals. The research sample of 30 to 80 respondents. The results of this study obtained and overview of diabetes self-management knowledge that is less than optimal, journal 1 (69.1%), journal 2 (58.4%), journal 3 (61.7%), journal 4 (50.0%). Conclusion: self management knowledge from education domain, dietary settings, pharmacology, physical exercise, blood sugar monitoring is not optimal. Suggestion: for nurses to do more education to people with DM and their families so that knowledge becomes more widespread. Keywords: self-management, diabetes mellitus, knowledge